2005
DOI: 10.1007/s10038-005-0336-7
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor CAG and GGC polymorphisms in Mediterraneans: repeat dynamics and population relationships

Abstract: Microsatellite variation (CAG and GGC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
40
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 21 publications
7
40
0
Order By: Relevance
“…The recent article by Rajender et al (2007) provides a nice review on the AR CAG and GGN repeats with respect to their function and their statistical association with a wide range of clinical phenotypes. Studies comparing the distribution of allele sizes for the CAG and GGN microsatellite repeat polymorphisms between different populations have noted shorter repeat lengths, on average, in men of African versus Caucasian descent (Kittles et al 2001;Esteban et al 2006). Consistent with the in vitro studies showing increased activity of the AR product with shorter AR CAG and GGN repeat alleles, studies have also found increased AR protein expression levels in prostatic tissues from men of African descent (Gaston et al 2003;Olapade-Olaopa et al 2004).…”
Section: Introductionmentioning
confidence: 59%
“…The recent article by Rajender et al (2007) provides a nice review on the AR CAG and GGN repeats with respect to their function and their statistical association with a wide range of clinical phenotypes. Studies comparing the distribution of allele sizes for the CAG and GGN microsatellite repeat polymorphisms between different populations have noted shorter repeat lengths, on average, in men of African versus Caucasian descent (Kittles et al 2001;Esteban et al 2006). Consistent with the in vitro studies showing increased activity of the AR product with shorter AR CAG and GGN repeat alleles, studies have also found increased AR protein expression levels in prostatic tissues from men of African descent (Gaston et al 2003;Olapade-Olaopa et al 2004).…”
Section: Introductionmentioning
confidence: 59%
“…This autosomal genetic study carried out in 15 anthropologically well-defined Mediterranean populations was designed to analyze population relationships and give complementary insight on that derived from previous genetic studies (Quintana-Murci et al, 2003;Esteban et al, 2006;Gerard et al, 2006;Olivieri et al, 2006;Gonzá lez-Pérez et al, 2007;Tomas et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple candidates have been suggested, including genes that aVect susceptibility to oxidative DNA damage, growthrelated pathways, androgen receptor signaling, chronic inXammatory responses, and RNA processing (Rennert et al 2005;Shand and Gelmann 2006;Sarma et al 2008;Zabaleta et al, 2008). Several of these candidate genes have been investigated for diVerential distribution of allelic variants that may aVect risk, and cohorts from Africa and those of African descent have the highest frequencies of the putative risk alleles (Esteban et al 2006;Kittles et al 2001;Zeigler-Johnson et al 2002). Of interest is that one study found an association with a CYP3A4 promoter variant in both African Americans and European Americans, but not in Nigerians, indicating the complexity of analyzing stratiWed data (Kittles et al 2002;Hainaut and Boyle 2008;Lessells and Cooke 2008) (Table 5).…”
Section: Prostate Cancermentioning
confidence: 98%